Carbon Capture, Employment, and Coming Home from Prison. Issue 1 (2nd January 2022) - Boman, IV, John H.; Smith, Adam J.; Saxe, Jennie; Righetti, Tara; Rony, Asif; Fan, Maohong; Mowen, Thomas J.
ABSTRACT: Finding and securing employment is a huge challenge for those who have been released from prison. In this paper, we argue that carbon capture technology carries the unique potential to positively impact employment opportunities for those who are undergoing the reentry process. Notably, these careers exist nearly entirely in industries which already employ ex-felons. If carbon capture technology were implemented throughout the United States, our estimates suggest that ex-felons would be eligible for nearly 3.6 million careers. Many of these jobs would be created in industries which directly or indirectly support natural resource extraction, ethanol production, electricity generation, and iron, steel, and cement production. In addition to benefiting the economy, these careers would provide returning individuals with financial security and supportive, prosocial peer relationships. Accordingly, carbon capture carries the unique ability to promote environmental justice while simultaneously providing relief to a tremendously overburdened criminal justice system.